Food safety training requirements and food handlers' knowledge and behaviors - Pilling, Valerie K.; Brannon, Laura A.; Shanklin, Carol W.; Roberts, Kevin R.; Barrett, Betsy B.; Howells, Amber D. (International Association for Food Protection, 2008)
Very little research has evaluated how different types of food safety training requirements in foodservice establishments affect food handlers' performance. Foodservice employees (n = 242) from randomly selected restaurants from three Midwestern states within a 300-mile radius of the research institution completed a survey to assess their food safety knowledge and important behavioral antecedents (e.g., attitudes, intentions) related to food safety. Employees’ compliance with three important food safety behaviors (handwashing, use of thermometers, and proper handling of food and work surfaces)was observed. This study evaluated the effectiveness of two alternative food safety training requirements by comparing knowledge, behavioral antecedents, and behavioral compliance rates between two groups of food handlers: a group from restaurants in which food safety training is mandatory for all food handlers and a group from restaurants in which only shift managers must be knowledgeable about food safety. Mandating training for all food handlers was associated with improved compliance with some food safety behaviors; however, requiring that shift managers be knowledgeable about food safety appears to contribute similarly to employees' knowledge, behavioral antecedents, and compliance with regard to the three important food safety behaviors observed.
Keywords: Food safety; Theory of planned behavior; Behaviors; Foodservice employees; Attitudes; Intentions